Aqueously altered igneous rocks sampled on the floor of Jezero crater, Mars - Farley,KA; Stack,KM; Shuster,DL; Horgan,BHN; Hurowitz,JA; Tarnas,JD; Simon,JI; Sun,VZ; Scheller,EL; Moore,KR; McLennan,SM; Vasconcelos,PM; et al. (Science, 2022)
The Perseverance rover landed in Jezero crater, Mars, to investigate ancient lake and river deposits. We report observations of the crater floor, below the crater?s sedimentary delta, finding the floor consists of igneous rocks altered by water. The lowest exposed unit, informally named Séítah, is a coarsely crystalline olivine-rich rock, which accumulated at the base of a magma body. Fe-Mg carbonates along grain boundaries indicate reactions with CO2-rich water, under water-poor conditions. Overlying Séítah is a unit informally named Máaz, which we interpret as lava flows or the chemical complement to Séítah in a layered igneous body. Voids in these rocks contain sulfates and perchlorates, likely introduced by later near-surface brine evaporation. Core samples of these rocks were stored aboard Perseverance for potential return to Earth.